Zusammenhalts-Regionen – zur Theorie der Weltgesellschaft in der Sozialgeographie - P. Dirksmeier (Copernicus Publications, 2021)
The essay combines the concept of social cohesion with Rudolf Stichweh's system-theoretical concept of world society. These two approaches are joint hereafter with questions of spatial differentiation. The aim is to embed empirical micro-studies in macro-theoretical terms and to make them useful for empirical research in social geography. The construct of “cohesive region” demonstrates this by using the example of neighbourhoods.